Al-Qur'an Dalam Prespektif Muhammed Arqoun (An analysis of Tafsir Arqoun's thought) (An analysis of Tafsir Arqoun's thought) - Imam Ghozali (STAIN Bengkalis, 2018)
Arkoun is one of contemporary Islamic thinkers with his applied Islamological ideas to compensate for western Islamology which he thinks is irrational of his approach, whereas classical Islamology has a weakness, ie not having a reflection on thought and methodology. He specializes in theology, philosophy, and law. According to Arkoun in the Muslim tradition of collecting al-Qur'an began at the time of the Prophet died in 632, but when he lived it seems certain verses have been written. Partial assemblies were made with somewhat unsatisfactory materials, because the paper was not yet known among the Arabs and was available to them only in the late eighth century. The death of the Companions of the Prophet, those who joined him from Mecca to Madinah in 622, and the sharp debate among Muslims encouraged the third Caliph, Usman, to collect the totality of revelation into a compilation called the Mushaf